2001
DOI: 10.1159/000046901
|View full text |Cite
|
Sign up to set email alerts
|

<i>L</i>-Arginine Immunoreactive Enteric Glial Cells in the Enteric Nervous System of Rat Ileum

Abstract: L-Arginine is a precursor of nitric oxide (NO) that may be involved in neuronal activity in the gastrointestinal tract. It is known that NO is formed from L-arginine by NO synthase which is localized in neurons in the enteric nervous system. The present study demonstrated that significant L-arginine immunoreactivity was present in the enteric ganglia. Ultrastructural examination showed that L-arginine immunoreactivity was present in the ganglionic glial cells but not in neurons. These findings suggest that ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Enteric glial-mediated neuromodulation Enteric glia can modulate enteric neural circuits in a number of ways, including terminating the actions of neurotransmitters from synapses, 57,58,60,61 supplying neurons with neurotransmitter precursors 11,62 and by generating neuroactive substances. 63 Removing neurotransmitters released at synapses is essential for the maintenance of normal neural activity.…”
Section: Enteric Glia 'Listen' To Neuronal Conversationsmentioning
confidence: 99%
“…Enteric glial-mediated neuromodulation Enteric glia can modulate enteric neural circuits in a number of ways, including terminating the actions of neurotransmitters from synapses, 57,58,60,61 supplying neurons with neurotransmitter precursors 11,62 and by generating neuroactive substances. 63 Removing neurotransmitters released at synapses is essential for the maintenance of normal neural activity.…”
Section: Enteric Glia 'Listen' To Neuronal Conversationsmentioning
confidence: 99%
“…In nonmyelinating Schwann cells penetrating the ENS with extrinsic nerves, expression is relatively low, whereas EGCs accompanying the intrinsic neurons express higher levels of this enzyme (Kato et al, 1990). Similar to astrocytes, EGCs also express vimentin (Jessen and Mirsky, 1983) and L-arginine (Nagahama et al, 2001) and are rich in glycogen granules.…”
Section: Localization and Phenotypic Characteristics Of Egcmentioning
confidence: 99%
“…Secondly, as EGCs are rich in glycogen granules, they may constitute a major source of glucose for enteric neurons, similar to that provided by astrocytes to CNS neurons (Koizumi, 1974;Cataldo and Broadwell, 1986). Thirdly, EGCs have recently been shown to be the only cells within the ENS that are immunoreactive for L-arginine (Nagahama et al, 2001), a substrate required for the nitric oxide (NO) synthesis. NO is a mediator of intercellular signaling and is considered an important neurotransmitter in the ENS since NO synthase (NOS) immunoreactive neurons account for 20%-30% of ENS neurons Llewellyn-Smith et al, 1992;Ekblad et al, 1994;Timmermans et al, 1994).…”
Section: Neuroprotective and Neuromodulatory Functions Of Egcmentioning
confidence: 99%
“…44 In fact, experimental human and animal studies have shown that enteric glial cells may also be involved in intestinal inflammation, 45,46 enteric neurotransmission [47][48][49] and, importantly, are essential for the homeostasis of enteric neurons. 50 With respect to this last aspect, a recent study showed that enteric glia disruption may alter the neurochemical coding of enteric neurons in an experimental animal model.…”
Section: Discussionmentioning
confidence: 99%